Skin irritation potential of graphene-based materials using a non-animal test. Issue 2 (12th December 2019) - Fusco, Laura; Garrido, Marina; Martín, Cristina; Sosa, Silvio; Ponti, Cristina; Centeno, Alba; Alonso, Beatriz; Zurutuza, Amaia; Vázquez, Ester; Tubaro, Aurelia; Prato, Maurizio; Pelin, Marco
Abstract : Graphene related materials, if prepared with non-irritant exfoliation agents, do not induce skin irritation on a 3D model of human epidermis, following the OECD guideline 439. Abstract : Besides inhalation, skin contact may be considered one of the most relevant exposure routes to graphene-based materials (GBMs). However, very few data on the cutaneous toxicity of these materials are available, so far. This study is focused on skin irritation potential of a panel of GBMs: few-layer graphene (FLG), exfoliated by ball milling of graphite, FLG exfoliated by ultrasonication using sodium dodecyl sulfate (FLG-SDS) or sodium dodecylbenzenesulfonate (FLG-SDBS), CVD-graphene, obtained by chemical vapor deposition, graphene oxide (GO) and reduced GO (rGO). Skin irritation was assessed using the SkinEthic™ Reconstructed human Epidermis (RhE), following the Organisation for Economic Co-operation and Development (OECD) Test Guideline (TG) 439. Even though not validated for nanomaterials, the OCED TG 439 turned out to be applicable also for GBM testing, since no interference with the methylthiazolyldiphenyl-tetrazolium bromide (MTT) reduction, used as a final readout, was found. Furthermore, direct epidermal exposure to powdered GBMs mimics the actual human exposure, avoiding interference by the cell culture medium (protein corona formation). Only GBMs prepared with irritant surfactants (FLG-SDS and FLG-SDBS), but not the others, reduced RhE viability at levels lower than those predicting skin irritation (≤50%), suggesting irritant properties. This result was further confirmed by measuring cytokine (IL-1α, IL-6 and IL-8) release by GBM-treated RhE and by histological analysis as additional readouts to implement the guideline. On the whole, these results demonstrate that GBMs prepared with non-irritant exfoliation agents do not induce skin irritation after a single acute exposure.